Contemporary Indo-Sri Lanka Relations from the Perspectives of Functionalism - Padmakumara, S. Chaminda (University of Colombo, 2015)
With the conclusion of the civil war in Sri Lanka, most of the ambiguities and contradictions in Indo-Sri Lanka relations have come to an end. It seems that both countries are moving towards a more cooperative and pragmatic approach through which they can sustain better bilateral relations. What history suggests is that Indo-Sri Lanka relations in high political realms are mostly passive and contradictory. By contrast, relations between the two nations in low political domains such as bilateral trade, resource exchange, technical collaboration and education have relatively prospered. Therefore, this study intends to examine how Indo-Sri Lanka relations can be further strengthened by adopting a functional agenda that mainly focuses on the practical necessities of the two nations while provisionally ignoring the politically sensitive matters. To this end, the study draws theoretical insights from functionalism that suggests a pragmatic approach for international cooperation. More precisely, functionalism emphasizes the need for countries to be cooperative either simply for technical purposes or for functional ends. It also centrally believes that cooperation in low political spheres can be more successful than cooperative endeavors in high political realms. Considering the relevance of functionalism to Indo-Sri Lanka relations, the study attempts to reveal new functional scopes through which both nations can gain mutual benefits. The methodology adopted in this study is twofold. A quantitative analysis has been incorporated to examine how Indo-Sri Lanka relations have been progressing in functional areas, particularly in bilateral trade relations and resource exchange during the last two decades. At the same time, archival sources have been utilized for the purpose of theoretical framing. Finally, key findings of the study suggest that Indo-Sri Lanka relations can be further sustained by implementing a functional agenda along with a careful selection of functional necessities.
Keywords: Bilateral relations, Functionalism, Functional cooperation, Low[politics